Cellular Location of HNF4α is Linked With Terminal Liver Failure in Humans. Issue 6 (21st April 2020) - Florentino, Rodrigo M.; Fraunhoffer, Nicolas A.; Morita, Kazutoyo; Takeishi, Kazuki; Ostrowska, Alina; Achreja, Abhinav; Animasahun, Olamide; Haep, Nils; Arazov, Shohrat; Agarwal, Nandini; Collin de l'Hortet, Alexandra; Guzman‐Lepe, Jorge; et al.
Abstract : Hepatocyte nuclear factor 4 alpha (HNF4α) is a transcription factor that plays a critical role in hepatocyte function, and HNF4α‐based reprogramming corrects terminal liver failure in rats with chronic liver disease. In the livers of patients with advanced cirrhosis, HNF4α RNA expression levels decrease as hepatic function deteriorates, and protein expression is found in the cytoplasm. These findings could explain impaired hepatic function in patients with degenerative liver disease. In this study, we analyzed HNF4α localization and the pathways involved in post‐translational modification of HNF4α in human hepatocytes from patients with decompensated liver function. RNA‐sequencing analysis revealed that AKT‐related pathways, specifically phospho‐AKT, is down‐regulated in cirrhotic hepatocytes from patients with terminal failure, in whom nuclear levels of HNF4α were significantly reduced, and cytoplasmic expression of HNF4α was increased. cMET was also significantly reduced in failing hepatocytes. Moreover, metabolic profiling showed a glycolytic phenotype in failing human hepatocytes. The contribution of cMET and phospho‐AKT to nuclear localization of HNF4α was confirmed using Spearman's rank correlation test and pathway analysis, and further correlated with hepatic dysfunction by principal component analysis. HNF4α acetylation, a posttranslational modification important for nuclear retention, was also significantly reduced in failing human hepatocytes when compared with normal controls. Conclusion: These results suggest that the alterations in the cMET‐AKT pathway directly correlate with HNF4α localization and level of hepatocyte dysfunction. This study suggests that manipulation of HNF4α and pathways involved in HNF4α posttranslational modification may restore hepatocyte function in patients with terminal liver failure. Abstract : Although drug induced liver injury (DILI) is a rare clinical event, it carries significant morbidity and mortality, leaving it as the leading cause of acute liver failure in the United States. It is one of the most challenging diagnoses encountered by gastroenterologists. DILI is also the most common single adverse event that has led to withdrawal of drugs from the marketplace, drug attrition and failure of implicated drugs to obtain FDA approval. The development of various drug injury networks have played a vital role in expanding our knowledge regarding drug, herbal and dietary supplement related liver injury. In this review, we discuss what defines liver injury, epidemiology of DILI, it's biochemical and pathologic patterns, and management.